Peran Tjong A Fie dalam Perkembangan Ekonomi dan Pendidikan di Kota Medan - Rostologi Bancin; Aditya Darma; Fikri Alkhairi (Medan Resource Center, 2024)
Tjong A Fie, bestowed with the title Majoor der Chineezen by the Dutch East Indies government, functioned as a regional head tasked with maintaining security and addressing issues within the Chinese community. He is chosen for this study due to his embodiment of multicultural values, disregarding race, religion, or ethnicity in aiding others. As an immigrant of Chinese descent, Tjong A Fie wielded significant influence over Medan's economic and educational landscapes. This research aims to scrutinize his role in these developments. Employing a library-based approach, findings unveil Tjong A Fie's substantial contributions to Medan's political and economic progress. Notable endeavors include providing financial backing for various architectural landmarks such as the Almashum Grand Mosque, Tua Gang Mosque, Jalan Bishop Church, and others. Additionally, he employed approximately 10,000 workers on his plantations, irrespective of their backgrounds, showcasing his commitment to inclusivity and societal advancement.